Mineralogical, microstructural and porosimetry analysis in three different clayey soils (2019)
Diffraction, scanning electron microscope and helium porosimetry techniques have been shown to be suitable for obtaining physical and mineralogical properties in soil samples. The X-ray fluorescence spectroscopy allows obtaining the elemental composition of the sample, while the X-ray diffraction technique permits obtaining a qualitative and quantitative composition of the soil minerals. On the other hand, scanning electron microscope shows the microstructure of the soil and the helium porosimetry measures the pore size, volume, distribution, density and other porosity-related characteristics of the material. This document presents the characterisation of three different clayey soils by an experimental plan that included mineralogical, microstructural and porosimetric tests. The soils used were bentonite, kaolin and a natural clay retrieved near to Bogotá city, Colombia. Results obtained from this study allow providing a better understanding of soil behaviour, which traditional mechanical tests do not explain.